Nanomaterial-Based Tumor Photothermal Immunotherapy - Xu, Peng; Liang, Feng (International journal of nanomedicine, 2020)
In recent years, photothermal therapy (PTT) particularly nanomaterial-based PTT is a promising therapeutic modality and technique for cancer tumor ablation. In addition to killing tumor cells directly through heat, PTT also can induce immunogenic cell death (ICD) to activate the whole-body anti-tumor immune response, including the redistribution and activation of immune effector cells, the expression and secretion of cytokines and the transformation of memory T lymphocytes. When used in combination with immunotherapy, the efficacy of nanomaterial-based PTT can be improved. This article summarized the mechanism of nanomaterial-based PTT against cancer and how nanomaterial-based PTT impacts the tumor microenvironment and induces an immune response. Moreover, we reviewed recent advances of nanomaterial-based photothermal immunotherapy and discussed challenges and future outlook.